Neuropathologic correlates of hippocampal atrophy in the elderly: a clinical, pathologic, postmortem MRI study. - Robert J Dawe (Public Library of Science (PLoS), 2011)
The volume of the hippocampus measured with structural magnetic resonance imaging (MRI) is increasingly used as a biomarker for Alzheimer's disease (AD). However, the neuropathologic basis of structural MRI changes in the hippocampus in the elderly has not been directly assessed. Postmortem MRI of the aging human brain, combined with histopathology, could be an important tool to address this issue. Therefore, this study combined postmortem MRI and histopathology in 100 elderly subjects from the Rush Memory and Aging Project and the Religious Orders Study. First, to validate the information contained in postmortem MRI data, we tested the hypothesis that postmortem hippocampal volume is smaller in subjects with clinically diagnosed Alzheimer's disease compared to subjects with mild or no cognitive impairment, as observed in antemortem imaging studies. Subsequently, the relations of postmortem hippocampal volume to AD pathology, Lewy bodies, amyloid angiopathy, gross infarcts, microscopic infarcts, and hippocampal sclerosis were examined. It was demonstrated that hippocampal volume was smaller in persons with a clinical diagnosis of AD compared to those with no cognitive impairment (P = 2.6 × 10(-7)) or mild cognitive impairment (P = 9.6 × 10(-7)). Additionally, hippocampal volume was related to multiple cognitive abilities assessed proximate to death, with its strongest association with episodic memory. Among all pathologies investigated, the most significant factors related to lower hippocampal volume were shown to be AD pathology (P = 0.0018) and hippocampal sclerosis (P = 4.2 × 10(-7)). Shape analysis allowed for visualization of the hippocampal regions most associated with volume loss for each of these two pathologies. Overall, this investigation confirmed the relation of hippocampal volume measured postmortem to clinical diagnosis of AD and measures of cognition, and concluded that both AD pathology and hippocampal sclerosis affect hippocampal volume in old age, though the impacts of each pathology on the shape of the hippocampus may differ.